Comparision of Clinical and Laboratory Parameters in Culture Proven and Unproven Early Onset Sepsis in NICU - Shrestha, S; Dhongol Singh, S; Shrestha, NC; Shrestha, RPB; Madhup, SK (Kathmandu University Medical Journal, 2015)
Backgroud Early onset sepsis remains a major cause for neonatal morbidity and mortality.Objectives The aim of this study was to describe and compare the clinical and laboratory characteristics of neonates in neonatal intensive care unit with culture positive and negative early onset sepsis and verify if there were any differences between the groups.Methods A one year comparative prospective study was conducted from January 2011 to January 2012 in neonatal intensive care unit (NICU), Dhulikhel Hospital, Kathmandu University Hospital (KUH).Results Out of 215 cases of suspected neonatal sepsis, 192 (89.30%) cases of early onset sepsis were admitted in neonatal intensive care unit. Out of which 82 cases (42.7%) had blood culture positive and 110( 57.3%) had culture negative but compatible with features of clinical sepsis. There were no cases of culture proven meningitis and urinary tract infections.The clinical characteristic did not show any statistical differences between the study groups except for seizure which was found to be high in culture positive cases (p= 0.041). The hospital stay in neonatal intensive care unit was significantly longer (p=0.02) in culture positive cases. As for the laboratory test there were no differences found between the two study groups except cases of meningitis was more in culture proven early onset sepsis (p=0.00). The overall mortality in early onset sepsis was 36.95%. The higher mortality of 64.7% was seen in culture positive cases but statistically not significant.Conclusion Clinical manifestation and laboratory test were insufficient to distinguish between neonatal infection with blood culture positive and negative sepsis, hence both culture positive and negative cases should be treated promptly and equally.Kathmandu Univ Med J 2013; 11(4): 310-314